De la estética subjetiva a la condición interpretativa: entre Kant y heidegger (2015)
By establishing a relationship between Kant’s aesthetics and Heidegger's hermeneutic perspective we can see a rethinking of conception of the world and of the human being that allows establishing similarities and contrasts. The reflections on art in Kant's Critique of Judgment allow seeing cracks in the whole system: the feelings of the beautiful and the sublime by bringing the powers destabilize the system. From Heidegger’s point of view these fissures lead to interpretive turn. The world is in a different relationship, without a subject, like a relationship between earth and sky, divinities and mortals. The human being is no longer subject, rests on his own mortality as an event of absence, for no reason. This is a historic shift mode of modernity postmetaphysical rational thought.